Peritoneal cavity lavage reduces the presence of mitochondrial damage associated molecular patterns in open abdomen patients. Issue 6 (December 2017) - Martinez-Quinones, Patricia A.; McCarthy, Cameron G.; Mentzer, Caleb J.; Wenceslau, Camilla F.; Holsten, Steven B.; Webb, R Clinton; O'Malley, Keith
Abstract : BACKGROUND: Mitochondrial damage-associated molecular patterns (mtDAMPs), such as mitochondrial DNA and N-formylated peptides, are endogenous molecules released from tissue after traumatic injury. mtDAMPs are potent activators of the innate immune system. They have similarities with bacteria, which allow mtDAMPs to interact with the same pattern recognition receptors and mediate the development of systemic inflammatory response syndrome (SIRS). Current recommendations for management of an open abdomen include returning to the operating room every 48 hours for peritoneal cavity lavage until definitive procedure. These patients are often critically ill and develop SIRS. We hypothesized that mitochondrial DAMPs are present in the peritoneal cavity fluid in this setting, and that they accumulate in the interval between washouts. METHODS: We conducted a prospective pilot study of critically ill adult patients undergoing open abdomen management in the surgical and trauma intensive care units. Peritoneal fluid was collected daily from 10 open abdomen patients. Specimens were analyzed via quantitative polymerase chain reaction (qPCR) for mitochondrial DNA (mtDNA), via enzyme immunoassay for DNAse activity and via Western blot analysis for the ND6 subunit of the NADH: ubiquinone oxidoreductase, an N-formylated peptide. RESULTS: We observed a reduction in the expression of ND6 the day after lavage of the peritoneal cavity, that was statistically different from the days with no lavage (% change in ND6 expression, postoperative from washout: −50 ± 11 vs. no washout day, 42 ± 9; p < 0.05). Contrary to expectation, the mtDNA levels remained relatively constant from sample to sample. We then hypothesized that DNAse present in the effluent may be degrading mtDNA. CONCLUSION: These results indicate that the peritoneal cavity irrigation reduces the presence of mitochondrial DAMPs in the open abdomen. It is possible that increased frequency of peritoneal cavity lavage may lead to decreased systemic absorption of mtDAMPs, thereby reducing the risk of SIRS. LEVEL OF EVIDENCE: Prospective study, Case Series, Level V.